Millet processing: prospects for climate-smart agriculture and transition from food security to nutritional security - Jayasree Joshi; Sivaranjani Shanmuga Kumar; Rahul Kumar Rout; Pavuluri Srinivasa Rao (Journal of Future Foods)
Millets, which are small-seeded grains, are classified under the Poaceae family and are known for their high nutritive content. Millets are a viable option for the global population in light of growing concerns about climate change due to their exceptional tolerance to a variety of abiotic stresses, such as drought, salinity, light, and heat. They have short growing periods and can be sustained in adverse weather conditions with less irrigation requirements. They encompass morpho-physiological, molecular, and biochemical characteristics that confer superior resilience to environmental stress. The millet grains have the potential to contribute to health and nutrition, rural employment, household incomes, rural and national economies, and sustainable environmental management. They are a rich source of both macro and micro nutrients. They contain a significant amount of bioactive substances, along with minerals such as iron, calcium, phosphorus, and zinc. Millets need to be processed for consumption and preparation to improve its nutritional and sensory properties. The major challenge in millet processing is due to the lack of proper processing machineries, presence of antinutritional factors and the poor shelf life of the flour due to high lipase activity. This limitation can be mitigated by using the appropriate processing methods. This article gives an insight into millet processing and value addition and its role in ensuring nutritional security through climate-smart agriculture.